Autologous platelet-rich plasma cured refractory osteomyelitis complicated with fracture: a case report - Jianxiang LIU; Mengxing LYU; Hao CHEN; Lilan GAO; Meikun HU; Guiqiu SHAN; Kexuan QU (Zhongguo shuxue zazhi, 2023)
Objective To share the experience of autologous platelet-rich plasma(PRP) combined therapy in successful treatment of refractory osteomyelitis with fractures in children. Methods One case of refractory osteomyelitis with fracture in children failed to respond to traditional treatment for more than 14 months. A total of 20 mL of whole blood was collected from the child, and 6 mL of PRP with 4 to 5 times concentration was prepared by secondary centrifugation. To prepare 2 cm×2 cm platelet concentrate gel (PG), 3 mL of PRP was mixed with a 0.3 mL activator which was then covered with an absorbable dressing. A three-way tube sprayed the remaining 3 mL of PRP and 0.3 mL activator into the surrounding tissues. Results The X-ray film of the patient followed up for 1 week showed that the fracture line was blurred, and the fracture end had obvious callus formation. The X-ray film reexamination at 4 months showed that the fracture end healed well, the fracture surface healed, and the osteomyelitis healed. Conclusion Autologous PRP has a good effect in the treatment of refractory osteomyelitis combined with fracture in children, which can provide a new method for clinical treatment.